Teaching People What They Already Know: Designing Game Design Courses - Weiller, Thais Arrias (Gamevironments, 2021)
Game Design is one of those skillsets that are difficult to clearly define, and it can feel like - and is often described as - an inherent part of human nature. We all play games in one form or another, and even when we play universally recognizable games we often make rule changes to said games to fit the type of experience we want to have. Local variations of playground games, and house-rules to popular board games, bear witness to the fact that game design is a practice that people participate in, without necessarily thinking of it as game design. Even though design is something natural, it still needs to be honed and developed further for those who would like to pursue game design as a more formal profession. This presents a challenge for game education: how do we identify and describe the knowledge and skills that many people already use inadvertently as amateurs, in order to help students see what they need to hone and practice to become expert game designers? This report will describe how we created a framework to create a new Game Design course in the Videogame Development undergraduate program at Pontifícia Universidade Católica do Paraná (PUCPR) in Brazil. Our approach to this challenge was to divide Game Design into four distinct areas: mechanics, systems, contexts, and progression.